Ajaran Sivaisme Dalam Teks Tattwa Jnana - I Made Hartaka (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Religion can direct a person towards the path of liberation. Various attempts can be made to achieve these goals. Shivaism as one of the understandings that is widely developed in the archipelago offers a way that can be guided by humans in living their lives in the world. In the tattwa jnana text, the figure of Shiva is a central figure in every stage of achieving goals. Siva even becomes the basis for belief and the highest goal attained by humans. Through mind control and complete meditation practice it becomes a vehicle for attaining life goals. Controlling human senses and thoughts is an important point in living life. Seeing this background, the author is interested in exploring how the teachings of sivaism in the Tattwa Jnana text will influence the way of thinking of Hindus. In addition, the author hopes to contribute in encouraging critical thinking towards religious teachings that have been studied in order to strengthen sraddha as a Hindu society.